Technological design of jacquard fabric and their functionalization - Kostajnšek, Klara; Bajrič, Špela; Bizjak, Matejka (Wydawnictwo Politechniki Łódzkiej, 2022)
Functionalization of fabrics allows us to influence the physical-mechanical properties by using special yarns that improve fabric's properties, such as elasticity [1,2], thermal regulation [3,4], protection against ultraviolet (UV) rays [5–7], etc. In addition, from a design point of view, the shape and size of the pattern, its frequency and area distribution are also important, not only as a visual effect, but also in terms of the above-mentioned properties [8–10]. The aim of the study was to determine how different weft yarns, the size of the pattern and weave affect the final properties of the jacquard fabric. Six jacquard fabrics were woven on the same warp with two different weft yarns (cotton, Lyocell Clima) in two different patterns and two groups of double twill weaves (stiched and unstiched). The results show that fabrics made of cotton have poorer mechanical properties and lower permeability than fabrics with Lyocell Clima weft. Double unstitched fabrics generally have poorer mechanical properties and UV protection factors (UPF), but better air permeability values. A statistically significant influence of the raw material was shown for thickness, mass, thermal conductivity, tensile strength and, in the case of the size pattern and weave, for air permeability, breaking and tear strength.
Keywords: functionalization; jacquard pattern; physical-mechanical properties; cotton; Lyocell Clima; funkcjonalność; wzór żakardowy; właściwości fizyko-mechaniczne; bawełna